Factors Affecting The Use Of Accounting Information In Business Micro Small And Medium In Makassar City - Kurniati (JEKAMI Journal of Accounting, 2022)
Accounting information applied at the MSME’s that is lacking is one of the factors that causes MSME’s to be dificult to develop even to failures that end business closure. This study aims to examine the factor that influence the accounting information applied at the MSME’s using business scale. company age. owner’s/manager education background and accounting training. In collecting data using questionnaires. The regression model used in this study is a multiple linear regression models with SPSS. The sampling method for the study used the Random Sampling method and the result is 45 MSME owner’s/manager in the city of Yogyakarta with an error rate of 16%. The result showed that company age and accounting training has experiented had positive and significant effect on accounting information applied at the MSME’s. While scale of business and owner’s/manager education background do not affect the accounting information applied at the MSME’s.